General Optimization Model of Modular Equipment Selection and Serialization for Shale Gas Field - Hong, Bingyuan; Li, Xiaoping; Cui, Xuemeng; Gao, Jingjing; Li, Yu; Gong, Jing; Liu, Huanying (Frontiers in Energy Research, 2021)
The potential technical and economic advantages and flexible operability of modular equipment make it increasing widely used in gas field production and development. In addition to considering the manufacturing process, the selection and serialization of modular equipment should be made according to the productivity prediction of a gas well, so as to meet the field demand to the greatest extent and enhance the flexibility of gathering and transportation system. This article proposes a method to determine the use planning of modular equipment in shale gas field. Considering the processing capacity, processing cost, floor area, construction cost of modular equipment, and the changes of market supply and demand, an optimization model is established. On the basis of the abovementioned model, the method of serialization of modular equipment is proposed. The effectiveness of the model is verified by an actual case study. It is proved that the model can optimize the layout of modular equipment, make the modular equipment run efficiently and economically, reduce costs, and increase efficiency. This study provides a reference for optimizing the equipment management strategy and promoting green production practice of shale gas production.